Использование результатов анкетирования врачей-стоматологов для профилактики осложнений, возникающих на этапах эндодонтического лечения зубов (LLC "Endo Press", 2020)
In clause results of questioning of doctors-stomatologists on problems эндодонтического treatments of a teeth are submitted. The received data testify to the lowest level of knowledge, use of inadequate methods and materials for root channels of teeth.